2005
DOI: 10.1300/j049v13n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Buying Behavior of Western European Food Retailers

Abstract: The aim of this study has been to analyze important aspects of buying behavior of food retailers, i.e., trade buyers' evaluation of product and vendor attributes, based on a number of background variables, when choosing a new supplier of an already well-known product category. The study encompassed the retailers' buying behavior for pork, fish and cheese products. By conducting a conjoint analysis in sixteen Western European countries (15 'old' EU Countries (except Luxemburg), plus Norway and Austria), it is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…By using the literature on relationship marketing and the previous literature previously indicated, different parameters were identified that are relevant for the analysis of factors motivating retailers to buy food from local suppliers in Tanzania; these serve as a guide to the framework. These parameters include: food quality, year round delivery, price and customer requests (Oberholtzer et al, 2014;Lin and Wu, 2011;Skytte and Blunch, 2001;Skytte and Blunch, 2005). Sandelowski (2010) argues that a study may begin with a theory about a target phenomenon or a framework for data analysis, but this does not mean that is has to stay within this framework.…”
Section: Discussionmentioning
confidence: 99%
“…By using the literature on relationship marketing and the previous literature previously indicated, different parameters were identified that are relevant for the analysis of factors motivating retailers to buy food from local suppliers in Tanzania; these serve as a guide to the framework. These parameters include: food quality, year round delivery, price and customer requests (Oberholtzer et al, 2014;Lin and Wu, 2011;Skytte and Blunch, 2001;Skytte and Blunch, 2005). Sandelowski (2010) argues that a study may begin with a theory about a target phenomenon or a framework for data analysis, but this does not mean that is has to stay within this framework.…”
Section: Discussionmentioning
confidence: 99%
“…Our research suggests that a market-oriented conceptualisation of the vegetable supply chain is inadequate as a way of addressing the challenges of a transition to a sustainable food regime. Inspired by previous IMP research that has investigated relationships and networks in fresh food supply (Abrahamsen & Håkansson, 2012;Hingley, 2005;Hingley & Hollingsworth, 2003;Hingley & Lindgreen, 2001;Machat, 2009;Skytte & Blunch, 2005) we show that shaping a sustainable market requires a denaturalisation of market doxa -a controversy to which IMP ideas can contribute.…”
mentioning
confidence: 70%
“…Andersen and Munksgaard (2009) investigated NPD processes that involved extensive collaboration and joint development meetings, with the supplier being regarded as a member of the product development team. A study of food retailers conducted across 15 European countries found that the active management of supplier/customer relationships was a critical issue (Skytte & Blunch, 2005).…”
Section: Network Research On the Food Sectormentioning
confidence: 99%
“…Our review of this literature suggests that vendor selection criteria for food retailers can generally be classified into four areas: issues pertaining to margin (Rao, McLaughlin, and Hawkes 1995), issues related to product categories, consumer demand/product turnover (McGoldrik and Douglas 1983), issues related to delivery and availability (Skytte and Blunch 2005), as well as issues of manufacturer-support (Leach, Liu, and Pelton, 2011) (see Figure 1). …”
Section: Supplier Choice Criteria Theorymentioning
confidence: 99%